2015
DOI: 10.1038/nature14975
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the synaptotagmin–SNARE machinery for neuronal exocytosis

Abstract: Summary Synaptotagmin-1 and neuronal SNARE proteins play key roles in evoked synchronous neurotransmitter release. However, it is unknown how they cooperate to trigger synaptic vesicle fusion. Here we report atomic-resolution crystal structures of Ca2+- and Mg2+-bound complexes between synaptotagmin-1 and the neuronal SNARE complex, one of which was determined with diffraction data from an X-ray free electron laser, leading to an atomic-resolution structure with accurate rotamer assignments for many sidechains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
596
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 318 publications
(702 citation statements)
references
References 86 publications
43
596
7
Order By: Relevance
“…Subsequently, Ca 2+ -independent fusion is monitored for a 1-min period, followed by injection of 500 μM Ca 2+ , and Ca 2+ -triggered fusion was monitored for an additional 1-min period (for more details, see Methods). Our system qualitatively reproduces the effects of synaptotagmin-1, Cpx, and their mutations, on both spontaneous release and evoked release that have been observed in cortical neuronal cultures (19,45).…”
Section: Resultsmentioning
confidence: 57%
“…Subsequently, Ca 2+ -independent fusion is monitored for a 1-min period, followed by injection of 500 μM Ca 2+ , and Ca 2+ -triggered fusion was monitored for an additional 1-min period (for more details, see Methods). Our system qualitatively reproduces the effects of synaptotagmin-1, Cpx, and their mutations, on both spontaneous release and evoked release that have been observed in cortical neuronal cultures (19,45).…”
Section: Resultsmentioning
confidence: 57%
“…52 Ca 2+ -independent role of SytI is also supported by its ability to facilitate close membrane apposition in vitro even in the absence of calcium binding [24][25][26] and the recent identification of Ca 2+ -independent SNARE-binding motifs. 53 Syt XI may similarly facilitate lysosome docking to the cell membrane. Such a mode of action of Syt XI would recapitulate our recent finding with an unrelated C2 domain containing protein called dysferlin, which facilitated injury-triggered lysosome exocytosis by tethering lysosomes to the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies using high-resolution NMR (37) and crystallography (38) suggest that the C2 domains of Syt1 mediate SNARE binding, making it unlikely that PKC-dependent changes in the linker affect SNARE binding directly. However, it was recently suggested that the linker undergoes a structural change (39) and might become sterically able to engage the SNAREs or membranes without any change in the bimolecular affinity as such.…”
Section: Potentiation Of Spontaneous Release Is Mediated By Multiple mentioning
confidence: 99%